Two-bit memory and quantized storage phenomenon in conventional MOS structures with double-stacked Pt-NCs in an HfAlO matrix. Issue 9 (11th February 2016) - Zhou, Guangdong; Wu, Bo; Liu, Xiaoqin; Li, Ping; Zhang, Shuangju; Sun, Bai; Zhou, Ankun
Abstract : Two-bit memory and quantized storage phenomenon based on double-stacked Pt-NCs in an HfAlO matrix. Abstract : A two-bit memory and quantized storage phenomenon are observed at room temperature for a device based on the traditional MOS structure with double-stacked Pt-nanocrystals (Pt-NCs). A 2.68 and 1.72 V flat band voltage shift (memory window) has been obtained when applying a ±7 V programming/erasing voltage to the structures with double-stacked Pt-NCs. The memory windows of 2.40 and 1.44 V can be retained after stress for 10 5 seconds, which correspond to 89.55% and 83.72% stored charges reserved. The quantized charge storage phenomenon characterized by current–voltage ( J – V ) hysteresis curves was detected at room temperature. The shrinkage of the memory window results from the decreasing tunneling probability, which strongly depends on the number of stacks. The traps, de-traps and quantum confinement effects of Pt-NCs may contribute to the improvement of dielectric characteristics and the two-bit memory behavior. The multi-bit memory and quantized storage behavior observed in the Pt-NCs stacks structure at room temperature might provide a feasible method for realizing the multi-bit storage in non-volatile flash memory devices.